In the company of the courtesan : [large type] : a novel - Dunant, Sarah (Random House Large Print, 2006)
Escaping the sack of Rome in 1527, with their stomachs churning on the jewels they have swallowed, the courtesan Fiammetta and her dwarf companion, Bucino, head for Venice. Yet as their fortunes rise, this perfect partnership comes under threat, from the searing passion of a lover who wants more than his allotted nights to the attentions of an admiring Turk in search of human novelties for his sultan's court. But Fiammetta and Bucino's greatest challenge comes from a young crippled woman, a blind healer who insinuates herself into their lives and hearts with devastating consequences for them all.